The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.649876
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers of Myeloid and Glial Cell Activation Are Correlated With Multiple Sclerosis Lesional Inflammatory Activity

Abstract: Multiple sclerosis (MS)-related inflammation can be divided into lesional activity, mediated by immune cells migrating from the periphery to the central nervous system (CNS) and non-lesional activity, mediated by inflammation compartmentalized to CNS tissue. Lesional inflammatory activity, reflected by contrast-enhancing lesions (CELs) on the magnetic resonance imaging (MRI), is effectively inhibited by current disease modifying therapies (DMTs). While, the effect of DMTs on non-lesional inflammatory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…As serum/plasma NfL levels increase with physiological aging (Disanto et al, 2017), the measured NfL concentrations were adjusted for effect of healthy aging as described previously (Masvekar R et al, 2021). Following age vs serum-or plasma-NfL equations from HC cohorts were used: ln(serum NfL) = 0.0177*Age + 0.9696 and ln(plasma NfL) = 0.0158*Age + 1.247.…”
Section: Adjustment For Effect Of Healthy Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…As serum/plasma NfL levels increase with physiological aging (Disanto et al, 2017), the measured NfL concentrations were adjusted for effect of healthy aging as described previously (Masvekar R et al, 2021). Following age vs serum-or plasma-NfL equations from HC cohorts were used: ln(serum NfL) = 0.0177*Age + 0.9696 and ln(plasma NfL) = 0.0158*Age + 1.247.…”
Section: Adjustment For Effect Of Healthy Agingmentioning
confidence: 99%
“…Serum and plasma samples from healthy controls (HC) and multiple sclerosis (MS) subjects were collected at Neuroimmunological Diseases Section (NDS), NIAID after informed consent under IRB-approved protocol (ClinicalTrials.gov: NCT00794352). The NfL levels measured in HC and MS subgroups were previously reported (Masvekar R et al, 2021) and are used in the current study only as a positive control of neuronal injury; the measurements of other COVID-19 prognostic biomarkers in these control samples were not reported previously. 378 serum or plasma samples were collected from 338 COVID-19 patients grouped into 3 independent cohorts (Figure 1, Table 1, and Supplementary Data File 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, another study found no correlation between baseline serum NfL levels and baseline EDSS. Interestingly, high baseline serum NfL concentrations predicted high EDSS levels at follow-up and at study end [ 318 ]. Not just flat concentrations, but the change in serum NfL levels has also been associated with a change in EDSS [ 306 , 310 ] scores.…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
“… 13 CSF biomarkers have also been identified for multiple sclerosis, Parkinson's disease and Alzheimers disease (AD). 14 , 15 AD is probably the most extensively studied, and in AD, the ratio of the content of amyloid beta peptide Aβ 42/ Aβ 40 has been used to predict cortical amyloid deposition. 16 Idiopathic normal pressure hydrocephalus (iNPH) may also show changes in Aβ 42 levels compared with age-matched controls.…”
Section: Introductionmentioning
confidence: 99%